Analisis Pemilihan Payment Gateway Menggunakan Metode Simple Additive Weighting (SAW) - S, Muhammad Ikhsan; Susanto, Erliyan Redy; Puspaningrum, Ajeng Savitri; Neneng, Neneng (Journal of Computer System and Informatics (JoSYC), 2024)
This research discusses the analysis of payment gateway selection using the Simple Additive Weighting (SAW) method. The criteria considered in this study include transaction costs, transaction speed, transaction security, and service availability. The objective of this research is to assist business owners and individuals in choosing the appropriate payment gateway based on their needs. The use of the SAW method enables a relative assessment of predefined criteria for each considered payment gateway. The results show that Finpay is the top choice of payment gateway, followed by Winpay and IPaymu. This study aims to serve as a practical guide for online businesses in improving performance and customer satisfaction through the optimal use of a payment gateway.